2019
DOI: 10.1080/2162402x.2019.1674605
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the TIGIT-PVR immune checkpoint axis as novel therapeutic option in breast cancer

Abstract: Immune checkpoints are intensively investigated as targets in cancer therapy. T-cell immunoreceptor with immunoglobulin (Ig) and ITIM domains (TIGIT) and its ligand poliovirus receptor (PVR) are recently emerging as novel promising targets in immunotherapy. Here, we show that high expression of PVR represents an independent prognostic marker being associated with poor outcome for breast cancer patients. Furthermore, PVR mRNA, as well as protein expression, is associated with more aggressive breast cancer subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 61 publications
(75 reference statements)
2
52
0
Order By: Relevance
“…3 d). This distinction is supported by studies reporting increased affinity [ 23 , 24 ] and motility [ 32 ] of specific motor proteins interacting with mono- or short glutamylated MTs. Particularly, Kinesin-2 showed higher motility when MTs were modified with short Glu chains [ 32 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3 d). This distinction is supported by studies reporting increased affinity [ 23 , 24 ] and motility [ 32 ] of specific motor proteins interacting with mono- or short glutamylated MTs. Particularly, Kinesin-2 showed higher motility when MTs were modified with short Glu chains [ 32 ].…”
Section: Discussionmentioning
confidence: 91%
“…b hCMEC/D3-cells grown to confluence on chamber slides were incubated with EVs from MDA-MB231 or MDA-MB468 control or TTLL plus cells for 16 h. Then, MDA-MB231 or MDA-MB468 control cells loaded with CellTracker™ Green CMFDA were added and after 4 h, green fluorescent cells were counted. Mean ± SD of eight different determinations are shown [23,24] and motility [32] of specific motor proteins interacting with mono-or short glutamylated MTs. Particularly, Kinesin-2 showed higher motility when MTs were modified with short Glu chains [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key finding of our paper is that the T-reg cells had a relatively higher TIGIT expression level in OS tumor. TIGIT and its ligand poliovirus receptor (PVR) have been emerging as novel promising targets in immunotherapy for many tumors such as breast cancer, lung cancer, hepatocellular carcinoma etc[4143]. Tian reported that blockade of TIGIT prevented NK cell exhaustion and elicited potent anti-tumor immunity[44].…”
Section: Discussionmentioning
confidence: 99%
“…Human NK cells, Tregs, memory T cells, and some CD8 + T cells, express TIGIT, while in the TME, tumor-infiltrating NK cells show upregulated TIGIT expression accompanied by decreased DNAM-1 levels. CD155 is barely expressed in healthy human tissues, but it is dramatically overexpressed in various cancers, being considered an independent prognostic marker for poor prognosis for patients with breast cancer ( 55 ). Binding of TIGIT with CD155 suppresses the NK cells' cytotoxicity and IFN-γ production, whereas blockade using an anti-TIGIT antibody could reverse this effect ( 56 ).…”
Section: The Key Nk Cell Checkpoint Receptors or Molecules That Contrmentioning
confidence: 99%